Contribution of CD24 polymorphisms to autoimmune disease: A meta-analysis. (1st September 2015) - Baek, Jihae; Kang, Soowon; Byeon, Hyeyoung; Woo Hwang, Kwang; Min, Hyeyoung
Abstract: Purpose: To determine the relationship between two CD24 polymorphisms, rs8734/rs52812045 and rs3838646, and autoimmune disease. Design: Meta-analysis. Methods: The Medline, EMBASE, Web of Science, and Cochrane Library databases were searched for studies reporting the association between CD24 polymorphisms and autoimmune disease. Two of the authors selected eligible studies and extracted and analyzed the data independently. Results: Compared with carriers of the C allele (CC, CT, CT+CC), individuals homozygous for the T allele (TT) and heterozygous (CT+TT) at rs8734/rs52812045 have a higher incidence of autoimmune disease, whereas rs3838646 is not associated with autoimmune disease. Subgroup analysis found an increased risk of multiple sclerosis with the TT vs. CC, TT vs. CT, and TT vs. CC+CT alleles. Conclusion: The CD24 polymorphism rs8734/rs52812045 contributes to the development of autoimmune disease. Highlight: CD24 polymorphism, rs8734/rs52812045 is associated with autoimmune disease. T allele carriers have a higher risk of autoimmune diseases than C allele carriers. CD24 polymorphism, rs3838646 is not associated with autoimmune diseases.